Usability Telecontextual Study for Nursing Students: Unfolding Case Study - Nurdina, Gina; Kusuma Putri, Tri Antika Rizki; Hayati, Suci Noor (KnE Life Sciences, 2021)
Telecontextual study is a remote guidance method using an online platform to help students understand competency test materials and updates on nursing cases. This study aims to identify the platform’s usability to increase critical thinking for prepared students facing UJIKOM. The design of this study was descriptive with a cross-sectional approach. The research population is 34 students of STIKep PPNI West Java. Data collection was done via the USE questionnaire with 13 statements. The method’s useability was described with univariate analysis. The majority of respondents said this application was easy to apply (70.6%). Almost all respondents stated that this application was suitable and improved the critical thinking skills of nursing students (91.2%). Based on statistical tests, all respondents said that this application is easy to remember (100%). More than half of the respondents stated that this application only had minor errors (67.6%). All respondents remain satisfied with this application, although it needs improvement in several aspects (100%). It can be concluded that this application has good usability, as evidenced by the high score of the five usability aspects. Application development by minimizing errors and fixing the settings following the user target is expected to increase this application’s usability and readiness on a larger scale. Keywords: Usability, Telecontextual, Unfolding Case Study